Desafios e expectativas dos discentes do curso de arquivologia da Universidade Federal do Pará - GUERREIRO, Josué Matos (2017)
This study aims to analyze the current perspectives and challenges of the course of Archivology of the Federal University of Pará, contemplating the practice and the scientific study that surpasses the simple formation of the professional archivist, as it demonstrates the definitions of consecrated authors and the result Of the surveys with the interviewees. Applied research is characterized as bibliographic, documentary, descriptive, qualitative and quantitative. The objective is to present the current perspectives of the students and challenges of the course of Archivology of the Federal University of Pará (UFPA). In order to carry it out, it unfolds in the following phases: brief historical survey on the archivology and its insertion in the Federal universities, mapping the main moments that marked the study of the discipline in Brazil; Case study at the Federal University of Pará, through the application of an online questionnaire, with open answers made to all undergraduates of the UFPA archivology course of the years 2012, 2013, 2014, 2015, 2016, to identify the perceptions of Learners of the course, analyze and discuss them, and thus better understand them. The result obtained points out that there are many challenges to be overcome by students, during and after graduation, little physical infrastructure, material resources, training courses, labor market, among others that do not contribute to the development of the archivist . As for the results, the research proved to be satisfactory, since the students and the academic community of the course, fight relentlessly for the full development and recognition of this professional before the society.